Investigating the involvement of public transport authorities in MaaS developments - Ibrahim Mubiru (Transportation Research Interdisciplinary Perspectives)
In recent years, a novel mobility concept that is known as Mobility-as-a-Service (MaaS) has emerged in several metropolitan regions. MaaS is presently conceived as a decisive concept in shaping how mobility services are accessed by the users. The relevance of this mobility concept is depicted with various leverages, ranging from offering seamless mobility networks to providing sustainable mobility environments. However, what is still lacking in scholarly research is to scrutinise the level of involvement of public transport authorities in MaaS developments. Therefore, this study investigates the role of these authorities in MaaS plans in three German metropolitan areas namely Berlin, Hamburg, and the Ruhr region (Ruhrgebiet). The investigation is conducted through unfolding relevant literature by employing the thematic analysis method. The findings demonstrate that public transport authorities from the investigated case study areas have displayed visible efforts in integrating public transport forms (e.g., trains, trams and buses) with micro-mobility forms (e.g., bike-sharing) and car-sharing services. But contrarily, there are still challenges in incorporating the use of shared rides (e.g., ride-sharing and ride-sourcing) in their MaaS schemes, and thus, an integrative framework among public transport authorities, private mobility providers and policymakers has been proposed to smoothen the MaaS development process.